Suara masyarakat Papua - McGrath, S.; Wiliam, D. (Center for International Forestry Research, 2004)
This film was shot on location in Manokwari District, Papua with local villagers living below the poverty line who shared their views about how to develop forest management that works for forests and the poor. In a forest at the farthest edge of Indonesia, a dawn chorus is cut short by a roar of heavy equipment and trees crashing in the distance. The people of Papua --a resource rich but cash poor island-- struggle to control their future. With government, they have negotiated legal rights to land they have held for generations. Yet even as they are freed from authoritarian plunder, they find themselves at the mercy of foreign investment and deceit. Voices of Papua brought dialogue from forests to boardrooms and back again. In theaters and homes across Indonesia, it sheds new light on a crucial experiment in decentralization.